Ulnar-Sided Wrist Pain in the Athlete: Sport-Specific Demands, Clinical Presentation, and Management Options. Issue 6 (June 2021) - Rios-Russo, Jose L.; Lozada-Bado, Lianette S.; de Mel, Sandra; Frontera, Walter; Micheo, William
Abstract: Ulnar-sided wrist injuries are common in sports that require repeated pronosupination, wrist radial/ulnar deviation, axial loading, and gripping equipment. Common anatomic structures affected include the triangular fibrocartilage complex, extensor carpi ulnaris tendon, distal radioulnar and ulnocarpal joints, and hamate bone. Presenting symptoms include pain with activity, swelling, possible snapping or clicking, and reproduction of symptoms with provocative maneuvers. Imaging may confirm or rule out pathologies, but abnormal findings also may present in asymptomatic athletes. Initial treatment is usually nonoperative with splinting, load management, activity modification, strengthening the components of the kinetic chain of the particular sport, and pain management. Surgery is usually indicated in ulnar-wrist pain pathology such as hook of hamate fractures and required in associated instability. Future research should address specific treatment and rehabilitation protocols, emphasizing the complete kinetic chain along with the injured wrist.